2021
DOI: 10.26693/jmbs06.04.193
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Lead on Reproductive Health of Men

Abstract: Lead does not succumb to biological decomposition, and its ability to accumulate in the body makes it a serious threat to the health of people and animals, while affecting the reproductive function. In most cases, poisoning with lead remains asymptomatic. In a number of studies the authors concluded that in men the level of lead in the blood more than >40 μg/dL leads to the disorder of reproductive functions, such as low libido, a small sperm volume, the amount of spermatozoa, an increase in the abnormal mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Several studies have demonstrated that lead exposure can adversely affect the reproductive system of both males and females [ 31 , 32 , 33 , 34 , 48 , 49 ]. In males, blood lead levels exceeding 40 μg/dL can cause a reduction in sperm count and changes in sperm volume, motility, and morphology [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that lead exposure can adversely affect the reproductive system of both males and females [ 31 , 32 , 33 , 34 , 48 , 49 ]. In males, blood lead levels exceeding 40 μg/dL can cause a reduction in sperm count and changes in sperm volume, motility, and morphology [ 15 ].…”
Section: Discussionmentioning
confidence: 99%